2020
DOI: 10.22541/au.158880257.72351495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sevanol and its analogues: chemical synthesis, biological effects and molecular docking

Abstract: Among acid-sensing ion channels (ASICs), ASIC1a and ASIC3 subunits are the most widespread and prevalent in physiological and pathophysiological conditions. They participate in synaptic plasticity, learning and memory as well as in the perception of inflammatory and neurological pain, making these channels attractive pharmacological targets. Sevanol, a natural lignan isolated from Thymus armeniacus, inhibits the activity of ASIC1a and ASIC3 isoforms and has a significant analgesic and anti-inflammatory effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Sevanol is a natural lignan isolated from thyme Armenia that has anti-inflammatory and analgesic effects, with specific targets not yet defined. However, chemically synthesized sevanol and its analogs have been demonstrated to affect ASIC1a and ASIC3 (Belozerova et al, 2020). Further studies have shown that sevanol has a binding site that can be occupied by FRRF-amide peptides, which are located in the central vestibule of the ASIC1a channel (Belozerova et al, 2020).…”
Section: Natural Organic Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…Sevanol is a natural lignan isolated from thyme Armenia that has anti-inflammatory and analgesic effects, with specific targets not yet defined. However, chemically synthesized sevanol and its analogs have been demonstrated to affect ASIC1a and ASIC3 (Belozerova et al, 2020). Further studies have shown that sevanol has a binding site that can be occupied by FRRF-amide peptides, which are located in the central vestibule of the ASIC1a channel (Belozerova et al, 2020).…”
Section: Natural Organic Mattermentioning
confidence: 99%
“…However, chemically synthesized sevanol and its analogs have been demonstrated to affect ASIC1a and ASIC3 (Belozerova et al, 2020). Further studies have shown that sevanol has a binding site that can be occupied by FRRF-amide peptides, which are located in the central vestibule of the ASIC1a channel (Belozerova et al, 2020). This observation suggests a possible mechanism by which sevanol inhibits ASIC1a, but further studies are needed to verify this possibility.…”
Section: Natural Organic Mattermentioning
confidence: 99%